Pengaruh Media Gambar Berseri Terhadap Capaian Perkembangan Kognitif Anak Usia 5-6 Tahun di TK Harapan Kita Yadika Kabupaten Labuhanbatu Selatan - Lusiana Lumbantoruan; Anita Yus (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
The research was conducted with the aim of knowing the effect of serialized image media on the achievement of cognitive development of children aged 5-6 years at TK Harapan Kita Yadika, Labuhanbatu Selatan Regency. His study used a type of experimental research with a Quasi Experiment design in the form of The Equivalent Time Sample Design. The study population consisted of all children aged 5-6 years at TK Harapan Kita Yadika Kindergarten as many as 2 classes. The sampling technique used simple random sampling technique with the consideration of taking one group randomly, namely Melati 1 class which amounted to 18 children. This research variable consists of independent variables, namely serialized images and dependent variables, namely the achievement of children's cognitive development. Data collection techniques using observation with observation sheet instrument. The data were analyzed using non-parametric statistics by means of the wilcoxon test with a real level of α = 0.05 with a critical value of 40. The results showed that there was a significant effect of serialized image media on the cognitive development outcomes of children aged 5-6 years at TK Harapan Kita Yadika South Labuhanbatu Regency. With the results of statistical calculations where the hypothesis test results show Jcount of 54.5. The hypothesis testing criteria used are the real rate α = 0.05, with dk = n-1 obtained Jtable of 40, so it can be concluded that Jcount (54.5) > Jtable (40). This means that Ha is accepted and Ho is rejected or means that serialized image media has a significant effect on the achievement of cognitive development of children aged 5-6 years at TK Harapan Kita Yadika Kindergarten, Labuhanbatu Selatan Regency.